(3JYdje GdeJYde aj WQjb GdJYdes - (3GdRQfhLj, HQgGf GdOjf, EHQGgje (B, (3cGf MjG b (B7s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd Ydi Hfi BOe HGdYde hGdYed adeG QCjJ cKjQG ef WdGH GdYde ai ReGffG jLOhf Edi GdYde hdGjUdhf hef efGaYg hKeQGJg ` hgi GdYed Hg hGdfTQ ` jMQehf deG Cfge CNWChG WQjbg hJQchG TQGFWg s
(3BNQgG (B:s
... (3aUd ajeG jLdH GdQRb hajeG jefY heG jRjO ai GdYeQ heG jfbU (B, (3hdG HO Cf jJYde TjFG ef GdWH(B, (3hjJHQc HGdBKGQ GdhGQOI ai GdWH GdJi LeYgG GdEeGe CHh GdYHGS GdeSJZaQj aj cJGHg GdeSei (B: (3HWH GdfHi Ydjg GdSdGe JeJs
(3JHUQI GdeDda (B:s
(3UQM GdHZOGOj aj gOjI GdYGQajf HGSeg (B( (3EHQGgje (B) 1\13 , (3hQHeG jchf JGL GdOjf GdfYeGf Hf EHQGgje GdRQfhLj GdCYdGe (B8\35s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\ 425s
(3cTa GdXfhf (B1\ 425s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs